Moving Poetry : Hong Kong Children's Poems - Srivastava, Sonal; Richards, Page; Lim, Shirley (Book collections on Project MUSE., 2001)
One book to be read two ways! This is a delightful collection of children's poems and includes ideas on inspiring creativity in young people. 160 children took part in poetry writing workshops led by a group of Hong Kong's foremost poets. Their poems shed an intriguing light on life in Hong Kong, seen by a new generation.